Association of Severity of Coexisting Patellofemoral Disease With Increased Impairments and Functional Limitations in Patients With Knee Osteoarthritis. Issue 4 (28th March 2013) - Farrokhi, Shawn; Piva, Sara R.; Gil, Alexandra B.; Oddis, Chester V.; Brooks, Maria M.; Fitzgerald, G. Kelley
Abstract Objective To evaluate the association between severity of coexisting patellofemoral (PF) disease with lower extremity impairments and functional limitations in patients with tibiofemoral (TF) osteoarthritis (OA). Methods Radiographic views of the TF and PF compartments, knee extension strength, and knee range of motion were obtained for 167 patients with knee OA. Additionally, knee‐specific symptoms and functional limitations were assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the Activities of Daily Living Scale (ADLS). Results Moderate/severe PFOA was associated with lower knee extension strength (mean ± SD 1.4 ± 0.5 Nm/body weight [BW]) compared to no PFOA (mean ± SD 1.8 ± 0.5 Nm/BW). Additionally, total knee range of motion was significantly lower for patients with moderate/severe PFOA (mean ± SD 120.8° ± 14.4°) compared to no PFOA (mean ± SD 133.5° ± 10.7°) and mild PFOA (mean ± SD 125.8° ± 13.0°). Moderate/severe PFOA and mild PFOA were also associated with less pain while standing (odds ratio [OR] 0.2, 95% confidence interval [95% CI] 0.1–0.7 and OR 0.2, 95% CI 0.1–0.6, respectively) on the WOMAC, and moderate/severe PFOA was associated with greater difficulty with going downstairs (OR 2.9, 95% CI 1.0–8.1) on the ADLS. Conclusion It appears that knees with more severe coexisting PF disease demonstrate features distinct from those observed in TFOA in isolation or in combination with mild PF disease. Treatment strategies targeting the PF joint may be warranted to mitigate the specific lower extremity impairments and functional problems present in this patient population.